Exploring Factors Affecting Entrepreneurial Attitude of University Students - S.R.Padma, (Archives of Current Research International, 2024)
Aim: Explore and analyse the factors affecting entrepreneurial attitude of university students. Research Design: Ex-post facto research design. Sample: Post graduate and Doctoral scholars of University. Methodology: A structured questionnaire was developed and applied as data collection tool to 751 students for this study. Results: Respondents generally exhibit a high need for achievement (83.25%) characterized by strong planning, resilience, willingness to sacrifice for goals, and openness to innovation. Variations in responses, particularly regarding problem-solving abilities, highlight areas where some respondents might benefit from additional support or training. Notable percentage of undecided respondents regarding the intention to start a company (34.00%) indicates that while there is a strong inclination towards entrepreneurship, some respondents may still be weighing their options or facing uncertainties.